2008
DOI: 10.1080/01930820802289656
|View full text |Cite
|
Sign up to set email alerts
|

Visual Tutorials for Point-of-Need Instruction in Online Courses

Abstract: This paper will discuss a method of incorporating demonstrations into online information and technology literacy courses. The demonstrations are designed to increase the visual component and to address point-of-need questions and problems. Also discussed will be experimentations with this method in other library services, such as electronic reference services, one-shot course-related instruction, subject research guides, and outreach to faculty for their own professional development and as a way to incorporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Point-of-need tutorials within subject or course guides can help to develop nursing students' information literacy skills and answer frequently asked questions (Kimok & Heller-Ross, 2008;Turnbull, Royal, & Purnell, 2011). There are short tutorials in the RN-to-BSN research guide based on common questions such as, "I have found the perfect article, but I can only get the abstract.…”
Section: Subject Guides and Tutorialsmentioning
confidence: 99%
“…Point-of-need tutorials within subject or course guides can help to develop nursing students' information literacy skills and answer frequently asked questions (Kimok & Heller-Ross, 2008;Turnbull, Royal, & Purnell, 2011). There are short tutorials in the RN-to-BSN research guide based on common questions such as, "I have found the perfect article, but I can only get the abstract.…”
Section: Subject Guides and Tutorialsmentioning
confidence: 99%
“…Most library screencast articles discuss software options for their creation, or give tips and instructions on how to create screencasts without mentioning accessibility considerations (Betty, 2008;Griffis, 2009;Price, 2010;Rethlefsen, 2009;Slebodnik & Riehle, 2009;Sparks, 2010). Others discuss the benefits and uses of screencasts, including their use and possible advantages in reference and virtual reference (Brumfield, 2008;Buczynski, 2009;Carr & Ly, 2009;Steiner, 2010), and in supporting students in online classes (Kimok & Heller-Ross, 2008;Lockerby & Stillwell, 2010). A few discuss issues such as measuring screencast use (Betty, 2009) or designing pedagogically effective screencasts for instruction (Oud, 2009;Tempelman-Kluit, 2006).…”
mentioning
confidence: 99%
“…For some students a performance support tutorial allows a specific task to be accomplished independently. For example, a student who is struggling to find resources can view a video that demonstrates a successful search strategy in a search tool appropriate for their topic (Kimok & Heller-Ross, 2008).…”
Section: Performance Support and Academic Librariesmentioning
confidence: 99%